PERAN LOKASI, BRAND IMAGE DAN HARGA DALAM MEMPENGARUHI KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN PADA WAROENG EBEER DI SITUBONDO - Septian Dwi Widiantoro; Randika Fandiyanto; Riza Rachman (Fakultas Ekonomi dan Bisnis, 2025)
Entrepreneurship is a process of building value and creating new products aimed at generating long-term profits while maintaining stable customer satisfaction. The objective of this study is to determine the effect of location, brand image, and price on customer loyalty through customer satisfaction as an intervening variable at Waroeng Ebeer in Situbondo. The sampling technique used is purposive sampling. Data analysis and hypothesis testing in this study were conducted using the Smart PLS 3.0 application. The test results indicate that location, brand image, and price have a significant positive influence on customer satisfaction. However, location, brand image, and price have a positive but not significant influence on customer loyalty. meanwhile, customer satisfaction has a significant positive effect on customer loyalty, and location, brand image, and price also have a significant positive impact on customer loyalty when mediated by customer satisfaction.